Curium(III) speciation in the presence of microbial cell wall components - Henry Moll (Elsevier, 2021)
Trivalent actinides such as Cm(III) are able to strongly interact with microbes and especially with bacterial cell walls. However, detailed knowledge of the influence of different cell wall components is somewhat lacking. For this investigation, we studied the formation of aqueous Cm(III) complexes with cell wall components (e.g., lipopolysaccharide, peptidoglycan, and plasma membranes) using time-resolved laser-induced fluorescence spectroscopy (TRLFS). For all systems, two specific Cm(III) complexes with the biomacromolecules were observed as a function of pH. Specifically, Cm(III) was found to bind to phosphate and carboxyl groups present in the structure of the biomacromolecules. Stability constants and luminescence parameters of the specific Cm(III) complexes were determined and are presented. The pH of the surrounding aqueous solution, the plasma membrane concentration, and proteins included in the crude plasma membrane fraction were found to significantly impact the complexation of Cm(III). The Cm(III) luminescence spectra with plasma membranes, cell wall polymers, as well as Gram-negative (Sporomusa sp. MT-2.99 and Pseudomonas fluorescens) and Gram-positive (Paenibacillus sp. MT-2.2) bacteria will be explained by linear combination fitting using the investigated components.